Income Inequality and Redistributive Government Spending. (IMF Working Papers; Working Paper, 2003)
The paper examines empirically the question of whether more unequal societies spend more on income redistribution than their more egalitarian counterparts. Theoretical arguments on this issue are inconclusive. The political economy literature suggests that redistributive spending is higher in unequal societies due to median voter preferences. Alternatively, it can be argued that unequal societies may spend less on redistribution because of capital market imperfections. Based on different data sources, the cross-country evidence reported in this paper suggests that more unequal societies do spend less on redistribution.